Hopf and zero-Hopf bifurcations in the Hindmarsh–Rose system - Buzzi, Claudio [UNESP]; Llibre, Jaume; Medrado, João (Springer Nature, 2016)
We prove the existence of the classical Hopf bifurcation and of the zero-Hopf bifurcation in the Hindmarsh–Rose system. For doing this, some adequate change in parameters must be done in order that the computations become easier.
Keywords: Hindmarsh–Rose burster; Hopf bifurcation; Periodic solutions